Pengaruh Media Mozaik Bentuk Geometri Terhadap Kecerdasan Visual-Spasial Anak Usia 5-6 Tahun - Icam Sutisna; Apriyanto A.J Pauweni; Sri Rahayu A. Humakor (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
This experimental quantitative research applied on-group pretest-posttest design. Based on a sample of 16, the children showed an increase in the average result of pre-test by 18.8, meaning that the child's spatial visual intelligence is in the category of developing. Meanwhile, the data from posttest obtained an average of 32, meaning that the child's spatial visual intelligence is in the category of developing as expected. These results proved that there is a significant effect before and after treatment. Based on the results of the t test on (ɑ) = 0.05 obtained ttable = 0.213 and t count = 20,09, which means tcount ≥ t table 20.09 ≥ 0.213 and in other words, H0 is rejected and H1 is accepted. Thus, the research hypothesis states that there is an influence of geometric shape mosaic media on visual-spatial intelligence of the children at TK Teratai Kindergarten in Huangobotu Village, Kabila Bone District, Bone Bolango Regency.